Pengaruh Teknik Audit Berbantuan Komputer (Aplikasi ATLAS) dan Pengalaman Auditor terhadap Kualitas Audit dengan Kompetensi Auditor sebagai Variabel Mediator - Umroh, Muhammad (Jurnal Manajemen Bisnis dan Keuangan, 2024)
This study aims to determine the effect of computer-assisted audit techniques, and auditor experience on quality with auditor competence as a mediator variable. The sample in this study consisted of auditors working at public accounting firms in Indonesia who use the ATLAS application as their audit tool. The data collection technique used a research questionnaire with a purposive sampling method. The analysis technique used the Structural Equation Modeling (SEM) method using SmartPLS 3.0 software. The results of this study indicate that TABK (ATLAS application) has a significant effect on quality and auditor experience has a significant impact on audit quality through auditor competence, but in this study auditor experience does not affect audit quality and the effect of TABK (ATLAS application) on audit quality through auditor competence is not supported. The results of this study have theoretical and practical implications that auditor competence can be a mediating variable between the relationship between auditor experience and audit quality and the use of the ATLAS application in its application as a computer-assisted audit technique can help auditors in producing audit quality.